L’influence de l’Union européenne sur les politiques infra-communautaires - Henry Bakis; Charlotte Ullmann; Philippe Vidal (Netcom)
The main question of this article is the European policy influence on the infra-Community policies. The Europeanization and convergence of public policies supported by Europe are the two main purposes of this demonstration.